1992
DOI: 10.1038/hdy.1992.60
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of reproductive systems in filamentous ascomycetes. I. Evolution of mating types

Abstract: In the ascomycete family of Sordariaceae both heterothallism (with two mating types) and homothallism (without mating types) are common. A population genetic model is made in an attempt to find out under which conditions evolution from one system to the other is conceivable. Analysis shows that evolution from hetero-to homothallism is possible but evolution from homo-to heterothallism is improbable. As in these haploid fungi self-fertilization has other consequences than in diploid organisms, homothallism seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Theoretically, there is more support for the transition from heterothallism to homothallism among a fungal population (29,30) and for a general unidirectional breeding system shift from obligate outcrossing to partial or predominant self-fertilization (20,28). In the subsection Fumigati, there are nearly 20 additional species with a described sexual cycle, 3 of which are functionally heterothallic while the rest are homothallic.…”
Section: Geiser Personal Communication)mentioning
confidence: 99%
“…Theoretically, there is more support for the transition from heterothallism to homothallism among a fungal population (29,30) and for a general unidirectional breeding system shift from obligate outcrossing to partial or predominant self-fertilization (20,28). In the subsection Fumigati, there are nearly 20 additional species with a described sexual cycle, 3 of which are functionally heterothallic while the rest are homothallic.…”
Section: Geiser Personal Communication)mentioning
confidence: 99%
“…The phenomenon was first observed because of the inability to isolate sporidia of one of the two mating types from certain strains of the pathogen (38,63,87,100). This mating-type bias was investigated for a number of possible causes, including spore killers and meiotic drive (83). However, inheritance in experimental crosses showed that the observed mating-type bias does not result from the presence of segregation distorters, but from the exposure of lethal recessive alleles leading to nonviable haploids (87).…”
Section: Mating-type Bias and Haplo-lethal Allelesmentioning
confidence: 99%
“…Diploid selfing is common in flowering plants (Charlesworth & Charlesworth, 1987) and in conifers (Sorensen, 1973 ;Sakai et al, 1989;Å gren & Willson, 1991 ;Hitchcock & Cronquist, 1984;Godfrey & Wooten, 1981). Haploid selfing occurs in homosporous ferns (McCauley et al, 1985 ;Soltis & Soltis, 1987) and filamentous ascomycetes (Nauta & Hoekstra, 1992) owing to fusion of gametes produced by the same haploid gametophyte. If selection occurs during the haploid phase, haploid selfing leads to the same population-level consequences as haploid apomixis.…”
Section: Discussionmentioning
confidence: 99%